Judges' Ratio Decidendi in Hate Speech Crime Decisions: A Study of Decision Number 255/Pid.Sus/2021/PN Jkt.Utr from an Islamic Criminal Law Perspective: Ratio Decidendi Hakim dalam Putusan Tindak Pidana Ujaran Kebencian: Kajian Putusan Nomor 255/Pid.Sus/2021/PN Jkt.Utr Perspektif Hukum Pidana Islam - Sadira, Allian; Anwar, Syahrul; Faizal, Enceng Arif (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2026)
The development of social media has increased the ease of disseminating information while simultaneously giving rise to criminal acts of hate speech that have the potential to disrupt social order. One application is reflected in the North Jakarta District Court Decision Number 255/Pid.Sus/2021/PN.Jkt.Utr which imposed a criminal sentence on the perpetrator of spreading provocative narratives through a WhatsApp group. This study aims to analyze the judge's legal considerations in the decision and examine them from the perspective of Islamic criminal law. The study employs a normative juridical method, utilizing a statutory, conceptual, and comparative approach. The results show that the judge's considerations focused on fulfilling the elements of Article 28 paragraph (2) in conjunction with Article 45A paragraph (2) of the ITE Law. From the perspective of Islamic criminal law, this act is considered a jarimah ta'zīr because it contains elements that spread hostility, threatening public order and human honor. This criminalization is in line with the objectives of maqāṣid al-syarī‘ah, especially in maintaining social welfare, honor, and stability.